Velvet antler polypeptide prevents the disruption of hepatic tight junctions via inhibiting oxidative stress in cholestatic mice and liver cell lines. Issue 11 (19th October 2020) - Li, Lihua; Yang, Fan; Jia, Rongjun; Yan, Pengfei; Ma, Liman
Abstract : The present study aims to examine the protective effects and mechanism of a velvet antler polypeptide (VAP) against lithocholic acid (LCA)-induced cholestatic liver injury in mice. Abstract : The present study aims to examine the protective effects and mechanism of a velvet antler polypeptide (VAP) against lithocholic acid (LCA)-induced cholestatic liver injury in mice. A 7.0 kDa VAP was orally administered at doses of 10 and 20 mg kg −1 day −1 . Hematoxylin and eosin (H&E) staining of the liver showed that VAP7.0 reduced LCA-induced infiltration of inflammatory cells and areas of necrotic hepatocytes. In addition, VAP7.0 greatly reduced the levels of alanine aminotransferase (ALT), total bile acid (TBA) and total bilirubin (TBIL) in LCA mouse serum and prolonged the survival time of mice with LCA. VAP7.0 reduced the production of reactive oxygen species (ROS), decreased malondialdehyde (MDA) and increased the superoxide dismutase (SOD) levels in LCA mice. VAP7.0 also reduced OGG1 expression, which is a biochemical indicator of oxidative stress. Mechanistic analysis revealed that VAP7.0 significantly inhibited LCA-induced disruption of tight junction integrity, as determined by observing the morphology of the bile canaliculus, and this finding was confirmed by observation of the bile canalicular structure and tight junction proteins Occludin and ZO-1 expression. Moreover, we also found that VAP7.0 maintained the stability of hepatic paracellular permeability, as determined by Evans blue dye assays and horseradish peroxidase (HRP) tracer distribution through inhibiting the activation of the PI3K pathway in LCA mouse livers. In addition, VAP7.0 ameliorated H2 O2 -induced barrier dysfunction and tight junction disruption via inhibiting the PI3K activity in human HepG2 and SMMC7721 cells, which was confirmed by the PI3K activator 740Y-P. H2 O2 disturbed the localization of the tight junction proteins ZO-1 and Occludin, resulting in the transfer of these proteins from the membrane to the cytoplasm of cells, whereas pretreatment of cells with VAP7.0 prevented the disruption of the localization of these proteins, as determined by immunofluorescence staining and western blot analysis. These results demonstrate that VAP7.0 reduces liver injury by inhibiting oxidative stress and maintains the stability of hepatic tight junctions via suppressing the activation of the intracellular signaling molecule PI3K in LCA mice and hepatocellular carcinoma cells.